Pengaruh Harga, Kualitas Layanan Dan Cita Rasa Makanan Terhadap Kepuasan Pembelian Di UMK Cak Willis Surabaya - Cahyono, Muhammad Dwi; Pudjianto, Agung; Mulyati, Diana Juni (STAI Denpasar Bali, 2025)
Micro, Small and Medium Enterprises are businesses that play an important role in the Indonesian economy, both in terms of the jobs created and the number of businesses. MSMEs are the main foundation in the community's economic sector. On the other hand, MSMEs also function as drivers of innovation and creativity at the local level. The purpose of this study is to see the influence of Price, Service Quality and Taste on purchasing satisfaction at MSME Cak Willis. This study is a quantitative study with data collected through questionnaires distributed to Cak Willis buyers with a total of 110 respondents. This study uses probability sampling techniques with random sampling methods. Instrument testing in this study uses classical assumption tests, namely linearity tests, normality tests, multicollinearity tests, and heteroscedasticity tests. For the analysis test, the t-test and determination coefficient test (R2) are used with multiple linear regression data analysis techniques. The results of this study indicate that the Price and Taste variables do not affect Purchase Satisfaction. While the Service Quality variable affects Purchase Satisfaction.